Evaluation of the tear strength, compressive resistance, and surface hardness of three commercially available bite registration materials: an in vitro study - Hariprasad, A; Samant, Trailokya Narayan Dhir; Mohammed, HS; Anand, M; Ayesha, Syeda (International Journal of Dental Materials, 2021)
Background: For making a successful prosthesis, it is essential to achieve harmony between the maxillomandibular relationship. The precision and occlusal quality of the prosthesis partly depends on interocclusal bite registration material. Interocclusal bite registration material plays an important role in recording and transferring of existing patient’s occlusal records. The procedure used to record and transfer interocclusal relation should be performed with the utmost care and understanding to prevent clinical error.Aim: This study aimed to evaluate the tear strength, compressive resistance and surface hardness of three commercially available bite registration materials.Material and Methods: Three types of commercially available bite registration materials, Bis-acrylate (BA), Polyvinylsiloxane (PVS), and Polyether (PE), were made in Dumbbell and cylindrical shaped samples to evaluate the tear strength and compressive resistance, respectively and were analysed using the universal testing machine. The surface hardness was assessed using a microhardness tester. The obtained data were subjected to statistical analysis using SPSS 16.0 version (Chicago, Inc., USA). ANOVA/Kruskal-Wallis test was used to compare study parameters among the groups. Tukey’s posthoc test was used for inter-group comparisons.Results: Bis-Acrylate exhibited the greatest tear strength, followed by Polyvinylsiloxane and Polyether showed the least tear strength. More compressive resistance was observed in Polyether followed by Bis-Acrylate and lowest in Polyvinylsiloxane. A similar pattern was seen in the surface hardness among the three materials.Conclusion: Bis-acrylate showed greater tear strength and surface hardness, and it can be considered a better bite registration material.